Evaluation of intracoronary stenting by intravascular optical coherence tomography - Bouma, B E (Copyright 2003 by Heart, 2003)
Background: Conventional contrast cineangiography and intravascular ultrasound (IVUS) provide a limited definition of vessel microstructure and are unable to evaluate dissection, tissue prolapse, and stent apposition on a size scale less than 100 μm. Objective: To evaluate the use of intravascular optical coherence tomography (OCT) to assess the coronary arteries in patients undergoing coronary stenting. Methods: OCT was employed in patients having percutaneous coronary interventions. Images were obtained before initial balloon dilatation and following stent deployment, and were evaluated for vessel dissection, tissue prolapse, stent apposition, and stent asymmetry. IVUS images were obtained before OCT, using an automatic pull back device. Results: 42 stents were imaged in 39 patients without complications. Dissection, prolapse, and incomplete stent apposition were observed more often with OCT than with IVUS. Vessel dissection was identified in eight stents by OCT and two by IVUS. Tissue prolapse was identified in 29 stents by OCT and 12 by IVUS; the extent of the prolapse (mean (SD)) was 242 (156) μm by OCT and 400 (100) μm by IVUS. Incomplete stent apposition was observed in seven stents by OCT and three by IVUS. Irregular strut separation was identified in 18 stents by both OCT and IVUS. Conclusions: Intracoronary OCT for monitoring stent deployment is feasible and provides superior contrast and resolution of arterial pathology than IVUS.